Environmental Sanitation And Patient Behavior In Tuberculosis Control: A Case-Control Study In Talise Health Center, Palu City - Mustafa, Mustafa; Sasmita, Hanum; Rizkaningsih, Rizkaningsih (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Environmental and behavioral factors can increase the transmission of Tuberculosis (TB) and worsen outcomes. The purpose of the study was to determine the relationship between environmental sanitation and patient behavior with the incidence of TB. This type of analytical survey research uses a cross-sectional approach. The research is located in the Working Area of the Talise Health Center, Palu City. The research sample was all TB cases recorded at the Talise Health Center as many as 40 cases. The ratio of cases to control was 1:1, so that the total sample was 80 respondents. The control came from the closest neighbors who had the same age and gender as the case group. Data analysis using univariate and bivariate with Chi-Square test. The results showed that environmental sanitation had an influence on the incidence of TB, non-qualified environmental sanitation had a 5.476 times greater risk of developing TB than qualified people (p = 0.001, OR = 5.476 [2,099-14,284]). Environmental sanitation that has a significant relationship is ventilation (0.002), occupancy density (0.004), temperature (0.004) and lighting (0.004). For patient behaviors that include attitudes and actions that influence the incidence of TB, negative attitudes have a 4.394 times greater risk of developing TB than those who have positive attitudes (p = 0.003, OR = 4.394 [1,709-11,295]). Meanwhile, bad actions had a 3.857 times greater risk of developing TB than those with good actions (p = 0.003, OR = 3.857 [1.526-9.750]). The significance of this study is that environmental sanitation and patient behavior have an influence on the incidence of TB.